Concurrent Paraspinous Myopathy and Myasthenia Gravis. Issue 4 (June 2017) - Romano, Alissa E.; Al-Qudah, Zaid; Kaminski, Henry J.; Katirji, Bashar; Salame, Karim
Abstract : Abstract: Paraspinous myopathy is a rare neuromuscular disorder characterized by selective involvement of the cervical, thoracic, or lumbar muscles. Leading clinical features include a bent spine or dropped head (antecollis). In myasthenia gravis (MG), patients may have camptocormia secondary to neuromuscular junction dysfunction of the paraspinal muscles, and this condition usually responds to acetylcholinesterase inhibitors or immunosuppressive treatments. However, concomitant MG and paraspinous myopathy with histologic and electrophysiologic evidence of myopathic changes of the paraspinal muscles has only been reported twice in the literature. In this case series, 5 patients with MG with paraspinous myopathy are reported. While neck and extension truncal weakness is not uncommon in MG, most often the weakness is due to neuromuscular junction dysfunction. Coexisting paraspinous myopathy and MG is under-recognized, is often resistant to mainstay treatments, and should be considered in patients presenting with neck or trunk extensor weakness.